Sex and Gender Driven Modifiers of Alzheimer’s: The Role for Estrogenic Control Across Age, Race, Medical, and Lifestyle Risks - Rahman, Aneela; Jackson, Hande; Hristov, Hollie; Isaacson, Richard S.; Saif, Nabeel; Shetty, Teena; Etingin, Orli; Henchcliffe, Claire; Brinton, Roberta Diaz; Mosconi, Lisa (Frontiers in Aging Neuroscience, 2019)
Research indicates that after advanced age, the major risk factor for late-onset Alzheimer’s disease is female sex. Out of every three AD patients, two are females with postmenopausal women contributing to over 60% of all those affected. Sex and gender related differences in AD have been widely researched and several emerging lines of evidence point to different vulnerabilities that contribute to dementia risk. Among those being considered, it is becoming widely accepted that gonadal steroids contribute to the gender disparity in AD, as evidenced by the ‘estrogen hypothesis’. This posits that sex hormones, 17β-estradiol in particular, exert a neuroprotective effect by shielding females’ brains from disease development. This theory is further supported by recent findings that the onset of menopause is associated with the emergence of AD-related brain changes in women in contrast to men of the same age. In this review, we discuss genetic, medical, societal and lifestyle risk factors known to increase AD risk differently between the genders, with a focus on the role of hormonal changes, particularly declines in 17β-estradiol during the menopause transition as key underlying mechanisms.